The kinetics of the process of lithium ions electrochemical intercalation into porous carbon material - Мандзюк, Володимир Ігорович; Нагірна, Надія Іванівна (Eastern-European Journal of Enterprise Technologies, 2013)
The method of electrode impedance spectroscopy allowed studying the kinetics of lithium ions electrochemical intercalation into the porous carbon material obtained by hydrothermal carbonization of plant materials at a temperature of 750 ° C. Based on qualitative and quantitative analysis of Nyquist diagrams it was determined that this process is phasic by nature, which lies in the formation of the solid layer, based on lithium fluoride and formation of non-stoichiometric phases of the LixC type, on the carbon particles surface. The equivalent electrical circuits were chosen for each of these phases, allowing the simulation of impedance spectrum in the whole frequency range studied. Physical interpretation for each element of the scheme is proposed. The dependences of the parameters of the equivalent circuit on the equilibrium potential of the LixC-electrode were obtained. Increasing degree of lithium ions intercalation leads to the growth of geometric size of the surface solid layer, accompanied by its resistance increase and volume reduction. At the final stage of implementation these two parameters do not undergo considerable changes, which is the evidence of its structure and properties stabilization. The coefficient of lithium ions diffusion in the electrode material was calculated and the analysis of its dependence on the degree of intercalation was carried out.